2018
DOI: 10.1080/10942912.2018.1506479
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origin traceability of foxtail millet based on the combination of multi-element and chemical composition analysis

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Geographical origin traceability of foxtail millet based on the combination of multi-element and chemical composition analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Magnesium is the main component of chlorophyll [ 53 ] and was identified in the seeds from 147 species, at concentrations between 34 and 910 mg/100 g, in line with other seeds [ 29 , 40 ]. High Mg contents (>395 mg/100 g) were detected in the seeds from Abelmoschus esculentus , Acacia nilotica , Cassia fistula , Commiphora wightii , Corchorus olitorius , Parkia javanica , Pterocarpus marsupium and Urena lobata , which are similar to those reported for barley [ 55 ] and millet seeds [ 56 ]. The highest Mg accumulation was noticed in seeds belonging to the Amaryllidaceae, Burseraceae, Caricaceae and Moringaceae families.…”
Section: Resultssupporting
confidence: 81%
“…Magnesium is the main component of chlorophyll [ 53 ] and was identified in the seeds from 147 species, at concentrations between 34 and 910 mg/100 g, in line with other seeds [ 29 , 40 ]. High Mg contents (>395 mg/100 g) were detected in the seeds from Abelmoschus esculentus , Acacia nilotica , Cassia fistula , Commiphora wightii , Corchorus olitorius , Parkia javanica , Pterocarpus marsupium and Urena lobata , which are similar to those reported for barley [ 55 ] and millet seeds [ 56 ]. The highest Mg accumulation was noticed in seeds belonging to the Amaryllidaceae, Burseraceae, Caricaceae and Moringaceae families.…”
Section: Resultssupporting
confidence: 81%
“…The proximate composition of FMF were moisture (5.94 ± 0.12 g/100 g), ash (1.39 ± 0.03 g/100 g), protein (11.65 ± 0.45 g/100 g), fat (3.48 ± 0.04 g/100 g), crude fiber (2.21 ± 0.03 g/100 g), carbohydrates (75.33 ± 0.53 g/100 g), and energy (379.23 ± 0.59 kcal/100 g) ( Table 3 ). Liang et al. (2018) reported that the values of ash (1.39 g/100 g), protein (10.28 g/100 g), fat (3.40 g/100 g), dietary fiber (2.37 g/100 g) for FMF.…”
Section: Resultsmentioning
confidence: 99%
“…The world's oldest crop is foxtail millet ( Austin, 2006 ). This crop has been cultivated in China for 8000 years and presently grown in semi-arid and tropical regions of Africa, Asia, Australia, South America and especially in China, India, Mali, Nigeria, and Niger ( Liang et al., 2018 ; Saleh et al., 2013 ). Foxtail millet has attracted research attention due to its short growing season, insect and disease resistance, high salinity stress tolerance, photosynthesis efficacy, nutritional and medicinal properties ( Adekunle et al., 2013 ; Liu et al., 2011 ; Vetriventhan et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The low contents of H. vulgare (barley) and the high contents of S . italica (millet) are characteristic of these seeds (Liang et al ., 2018; Obadi et al ., 2021). Remarkable high Mg contents (>400 mg/100 g) were observed in the seeds from P. sumatrense , S. italica , C. tetragonoloba , S. alata and S. obtusifolia .…”
Section: Resultsmentioning
confidence: 99%